DIGITAL SOCIAL RESPONSIBILITY DAN NIAT PEMBELIAN: PERAN KESADARAN DAN KEPERCAYAAN MEREK SERTA SIKAP KONSUMEN - Nugroho, Jawad; Leki, Regina Destia; Kurniawati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to provide practical insights for companies in designing more effective DSR strategies to build positive attitudes, strong subjective norms, and supportive behavioral control. The development of digital technology, especially after the COVID-19 pandemic, has encouraged the transformation of Corporate Social Responsibility (CSR) from physical CSR to Digital Social Responsibility (DSR). In this context, the research focuses on analyzing the influence of DSR on consumer purchase intention in the Jabodetabek area. This study also explores the mediating role of brand awareness, brand trust, and attitude in strengthening the relationship between DSR and purchase intention. Using the Theory of Planned Behavior (TPB) framework, this study examines how DSR elements contribute to the formation of these mediating variables that influence consumer decisions. This study uses a quantitative approach using an interview questionnaire distributed to internet users who have understood the CSR responsibility obligations of a company. The sample used was 258. The data was processed using the SEM PLS method. The results of this study indicate that Digital Social Responsibility (DSR) has a significant positive effect on Brand Awareness, Brand Trust, Attitude, and Purchase Intention, with Brand Awareness also proven to mediate the relationship between DSR and Purchase Intention.